British Reception of L.N. Tolstoy’s Works in the Threshold of “Russian Boom” of the 1910s - Valentina S. Sergeeva (Studia Litterarum)
Foreign literature usually enters the field of the other culture obeying certain rules, including readers’ willingness, due to various reasons (political, social, psychological, etc.) to receive just these or those components. Such fragmentation, more or less, is overcome by the efforts of translators, commentators, researchers, critics; if the interest in the other culture is strong enough, the reader sees a relatively coherent picture, though not necessarily it is absolutely true. For many years Russian literature, first regarded as semi-barbarous and then considered to be high, was such an area of exotic interest for the English-speaking readers. Having entered the British range of reading, Leo Tolstoy became one of the cult foreign figures in the United Kingdom. Tolstoy’s reception included several layers: he was read as a bright representative of a foreign culture mainly known through stereotypes, as a great heir of the tradition of the European novel, as a progressive social activist whose creative work achieved the special meaning in the course of the political struggle, as the personified rebuff to the French naturalism and as an earnest religious philosopher leading the others by his example. Selective reception, namely, what caught the eye of the English-speaking auditory first of all, helps us reveal the specifics of the reading of Tolstoy’s works in Britain.